KONDISI VEGETASI DI KAWASAN HUTAN KEBUN RAYA BALIKPAPAN [Vegetation in the Forest at Balikpapan Botanical Garden] - Hidayat, Syamsul (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Balikpapan Botanical Gardens (East Kalimantan) is an ex situ conservation area where some parts of its land is originated from the Sungai Wain Protection Forest. Most of the area had been burned in 1982 and 1998. For the development of botanical gardens, vegetation condition/status assessment in forest areas is needed. The study was conducted by sampling with nested plot. Ten observations transects, each consisting of five plots measuring 20 m x 20 m set at ten locations which were supposed to represent the community. Results of the study showed that the quality of the vegetation in general was low, with medium category for conservation index and less category for diversity index. The vegetation was dominated by pioneer species that were less in conservation value such as Macaranga spp., Melicope glabra (Blume) T.G.Hartley and Calicarpa sp. There were 56 individual trees of nine species of Dipterocarp family -which is the regions native plants- found within this area. As for seedling stage, it was also dominated by pioneer species and shrubs. Species enrichment through the development of botanical garden, are expected to increase the value of biodiversity and conservation index.